Proceedings SIMTECT 2010 - Stothard, Phillip; Laurence, D. (SIMTECT, 2010)
The generation, retention, and transfer of knowledge are crucial for sustainability. Sustainable mining ensures efficient resource extraction with minimum social and environmental impact. The Mining Industry is well placed to leverage existing simulation infrastructure and apply it to sustainability. The application of existing simulation technology to multiple mining processes can reduce the cost of ownership. Interactive Visual Knowledge Management Systems present an opportunity for historic, current and future mining experience to be recorded and interrogated in a visual environment. Techniques such as digital-photography, 360 degree video, web-based communications, satellite imagery, computer graphics and sensor technology are readily available as a resource for storage, interrogation, interpretation and presentation of mining data. Mining data has been presented in 3D for sometime, however its application to sustainability is relatively new and an issue is that knowledge and understanding often resides with individuals, teams or as repositories of text based documentation. Discipline experts are extremely proficient at dealing and interpreting their own data sets. Unfortunately, when the time comes to present data or work with data from other disciplines, or more importantly, present information to stake holders and non-technical people, key information can be ‘lost in translation’.This presents an obstacle for community engagement where one person’s perception of a dataset may not necessarily be the same as another. The result can be conflict. Information should be easily interpreted and understood by all. That is, one person’s data should be easily available for others to learn from. Perception and understanding from one person to the next should be constant. Interactive Visual Knowledge Management Systems provide intuitive ways to analyse data and develop ‘Best-Practice’ for new mine operations. They offer a mechanism for people to take site tours without having to visit the real site. The cost savings when numerous people are involved in the decision making process can be great. The School of Mining Engineering at the University of New South Wales has developed an Interactive Visual Knowledge Management System for sustainability issues related to mining an ore-body in a sensitive area. This paper discusses the concept of that system, its objectives and presents the first trial of the prototype system. The results from this first trial are encouraging.